Potencial produtivo de capim-braquiária, desempenho de bovinos e digestibilidade de leguminosas em sistemas silvipastoris - COSTA, Suellen Brandão de Miranda (2015)
Silvopastoral systems (SPSs) refer to the production techniques in which integrate animals, forage plants and trees in the same area, with the association of trees within cattle grazing areas or raising animals within the forest stands. This study aimed to evaluate quantitative factors of the forage and the cattle performance, in Brachiaria decumbens Stapf. pastures, as well as in situ digestibility of Gliricidia sepium and Mimosa caesalpiniifolia in increasing levels of inclusion in diets, also was estimate the consumption and the percentage of C3 species in the diet, in monoculture and under SPSs. The experiment was conducted at the Experimental Station of Itambé, at the Agronomic Institute of Pernambuco (IPA) for 24 months. The experimental area consisted of nine paddocks with 1.0 ha each, treatments: B. decumbens + Mimosa caesalpiniifolia or Gliricidia sepium consortium and B. decumbens in monoculture, in a randomized block design with three replications. Were used crossbred (Holstein x Zebu) males in continuous stocking. In each 28-day grazing periods were evaluated mass and forage allowance, stocking rate, average daily weight gain and per area weight gain, and, in cycles of 14 days, was evaluated the forage accumulation rate. The stable isotopic composition (δ13C‰) were analyzed in Center for Nuclear Energy in Agriculture. The total forage mass of Brachiaria in monoculture (5.091kg ha -1 DM) was higher (P≤0,05) than in the SPS (3.964 kg ha-1 DM), while for green mass (dry matter base), the SPS had higher average values (2.237 kg ha-1 yr GDM) in relation to braquiária under monoculture (1.934 kg ha-1 yr GDM). The forage accumulation rate, forage allowance, stocking rate, daily weight gain and weight gain per area did not differ among the treatments, with average of 45,6 kg ha-1 day-1; 2,9 kg GDM/ kg LW; 1,8 AU ha-1; 0,6 kg-1 AU-1 day-1 and 33,1 kg ha-1 28 days, respectively. Increasing levels of gliricídia inclusion in the diets with braquiária allowed higher in situ digestibility of dry matter in all the incubation times. Only between the levels of 75 to 100% of inclusion gliricídia there was no statistical difference (P≥0,05). In relation to the incubation times, bellow 96 hours there were no differences between the levels of 50 and 100% of inclusion gliricídia, but favored the increase in digestibility. Reductions in in situ digestibility coefficients of MS were observed with increasing levels of inclusion sabiá. No significant differences were observed between the consumption of braquiária in monoculture, compared to the its consume under the SPS, in diets with 75% of and 25% gliricídia. The δ13C‰ values in the feces of cattle, indicate the predominance of C4 plants in the diet of the animals in all treatments, probably the predominance of C4 was due to Brachiaria decumbens consumption in all pastures. There was a greater presence of C3 in the cattle feces from SPS with gliricidia. The silvopastoral systems favored the B. decumbens due the higher amounts of green dry matter compared to monoculture ones. To the animal performance both SPS and in monoculture can be recommended, but SSPs system can present higher production efficiency due to timber production simultaneously with livestock production. The inclusion of gliricídia in ruminant diet under SPS with Brachiaria decumbens can promote increases in dry matter digestibility, whereas the sabiá reduces digestibility and during the dry season cattle can increase the intake of C3 species.